2018
DOI: 10.1002/fuce.201700094
|View full text |Cite
|
Sign up to set email alerts
|

Selected Review of the Degradation of Pt and Pd‐based Carbon‐supported Electrocatalysts for Alkaline Fuel Cells: Towards Mechanisms of Degradation

Abstract: It is usually believed that carbon‐supported electrocatalysts are stable in alkaline environment, owing to the better thermodynamics stability of many metals and oxides at high pH. By focusing on a selected literature review concerning Pt/C and Pd/C nanoparticles, and in particular from identical‐location transmission electron microscopy (ILTEM), it is demonstrated that this “common knowledge” is erroneous in aqueous alkaline electrolytes: both Pt/C and Pd/C suffer pronounced loss of electrochemical surface ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
107
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(112 citation statements)
references
References 87 publications
(152 reference statements)
5
107
0
Order By: Relevance
“…In agreement with past studies [33][34][35][36][37][38][39][40] , the bands at 1380-1390 cm -1 and 1310 cm -1 were assigned to carbonate ions (CO 3 2-) and bicarbonate ions (HCO 3 -), respectively. For all the electrocatalysts, the intensity of the carbonate features increased along with an increase of the electrode potential: this strongly supports our former assumption 25 that the degradation of Pt/C NPs involves the production of carbonate ions. The impact of the Pt wt.…”
Section: -2010 Hydroxide/oxide Adsorption On Goldsupporting
confidence: 86%
“…In agreement with past studies [33][34][35][36][37][38][39][40] , the bands at 1380-1390 cm -1 and 1310 cm -1 were assigned to carbonate ions (CO 3 2-) and bicarbonate ions (HCO 3 -), respectively. For all the electrocatalysts, the intensity of the carbonate features increased along with an increase of the electrode potential: this strongly supports our former assumption 25 that the degradation of Pt/C NPs involves the production of carbonate ions. The impact of the Pt wt.…”
Section: -2010 Hydroxide/oxide Adsorption On Goldsupporting
confidence: 86%
“…[24][25][26] In addition, carbon-supported Pt nanoparticles are not stable when cycled in potential in the stability domain of water, essentially because Pt assists the local corrosion of the carbon substrate, which destroys the anchoring point of the nanoparticles and leaves them unattached to carbon, leading to pronounced nanoparticles detachment and thus of severe electrochemical surface area (ECSA) loss. [27][28][29][30] Zadick et al demonstrated similar (although less pronounced) effects for Pd/C nanoparticles 31 , and showed that shaped Pd nanoparticles were also unstable in mild alkaline degradation tests 32 , being incapable to maintain their (cubic) shape upon potential cycling. Strasser et al ended to similar conclusion for octahedral PtNi nanoparticles in acidic environments 33 .…”
Section: Introductionmentioning
confidence: 91%
“…Electrochemical measurements of the activity of both amorphous and crystalline Pr 6 O 11 electrodes were performed towards usual reactions of electrocatalysis (namely the hydrogen evolution reaction (HER), oxygen evolution reaction (OER), and the oxygen reduction reaction (ORR), the latter one performed in absence or presence of a strong reducer in solution (NaBH 4 ) for potential application in direct borohydride fuel cell cathodes [16,72,[88][89][90]). They were performed in a Pyrex ® -based four-electrode cell, with glassy-carbon as the counter electrode (to avoid any possible contamination of the working electrode (WE) with the dissolution of the, usually Pt-based, counter electrode [91], a very likely occurrence in base electrolytes [92][93][94][95]), Pt as the auxiliary electrode, a hydrogen reference electrode (all the potential values are expressed on the RHE scale hereafter) and Pr 6 O 11 /GC (either bare (amorphous) or heat-treated (crystalline)) as the WE. The cell is equipped with an internal PTFE beaker to limit contamination by the possible dissolution of the Pyrex in strong base [96].…”
Section: Microstructural and Electrochemical Characterizationmentioning
confidence: 99%